ANALYSIS OF PHARMACOTHERAPEUTIC APPROACH IN PATIENTS WITH HYPERTHYROIDISM - Đokić, Ana; Djokic, Milena; Rovcanin, Branislav; Medic Brkic, Branislava (Medicinski podmladak, 2022)
Introduction: Hyperthyroidism represents a condition that occurs due to increased synthesis of thyroid hormones (T3, T4). In 90% of all cases it is caused by: Graves disease, toxic multinodular goiter and toxic adenoma. Therapy of hyperthyroidism includes medication, radioiodine treatment and surgery. The most prescribed antithyroid drugs belong to the thioamide group (thiamazole and propylthiouracil).Aim: The aim of this study was to analyze the preoperative pharmacotherapeutic approach with the use of 3 drugs from the thioamide group (PTU® (propylthiouracil), Thyrozol® (thiamazole) and Tiastat® (thiamazole)) in patients with hyperthyroidism.Material and methods: The study was conducted as a retrospective study among 62 patients aged 18 to 84 years, who reported to the Center for Endocrine Surgery KCS for the operative treatment of hyperthyroidism in period of 2014-2019.Results: Diagnosis of Graves disease was detected in 35.48% of patients, 32.26% had toxic multinodular goiter, and 32.26% toxic adenoma. The most patients (45.16%) were prescribed Tiastat®, 29.03% of them were prescribed PTU®, and 25.8% of them Thyrozol®. The most of patients suffered from Graves disease were treated with Tiastat®, those suffered from toxic adenoma with PTU® and with toxic multinodular goiter with Tiastat®. The most commonly used doses were 100 mg/day for PTU®, 20 mg/day for Tiastat® and 20 and 30 mg/day for Thyrozol®. Total thyroidectomy is most commonly performed in patients treated with Tiastat® and hemithyroidectomy in those treated with PTU®.Conclusion: The most of patients were prescribed Tiastat®. It was observed that there was a statistically significant difference (p˂0.05) in the use of individual drugs regarding to diagnosis, total daily dose of drug, BMI and type of surgical procedure.Key words: hyperthyroidism, pharmacotherapy, thiamazole, propylthiouracil, thyroidectomy